STUDENTS CAREER MOTIVATION AND TRACER STUDY REALITY: RECOMMENDATIONS FOR BUILDING ENGINEERING EDUCATION CURRICULUM DEVELOPMENT - Noviyanti, Rina; Nizard Rahwany, Khaylany; Ibtida Al Bukhori , Ghaza; Rajif Jamil Jusuf , Muhammad; Dwi Anggraeni , Yuni Dwi Anggraeni (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
This study aims to analyze intrinsic-extrinsic motivation in the career interest tendencies of BuildingEngineering Education students of Universitas Pendidikan Indonesia, map the profile of graduates basedon tracer study data, and correlate student career expectations with the reality of tracer study toidentify gaps and recommend curriculum development. This study used a descriptive-comparativequantitative approach method. Primary data collection techniques through career interestquestionnaires distributed to on-going students and secondary data from tracer study archives. Dataanalysis was carried out descriptively using Microsoft Excel to visualize the distribution of motivationand graduate profiles. Then, comparing the two results to assess the suitability between studentaspirations and actual conditions in the field. From the results, it was found that intrinsic motivation ismore dominant, although financial incentives remain a crucial consideration. In addition, the profile ofgraduates is dominated by consultants and contractors with the highest average income in contractors,and the concentration of work in Java, but as many as 22.74% of alumni are not working, indicating animbalance in the absorption of graduates. There is also a gap between student expectations and alumnireality such as income and career preference as a contractor which is not in line with the increasingtrend in the number of consultants.